The role of ultrasound in enhancing mesenchymal stromal cell-based therapies. (10th March 2020) - Liu, Daniel D.; Ullah, Mujib; Concepcion, Waldo; Dahl, Jeremy J.; Thakor, Avnesh S.
Abstract: Mesenchymal stromal cells (MSCs) have been a popular platform for cell-based therapy in regenerative medicine due to their propensity to home to damaged tissue and act as a repository of regenerative molecules that can promote tissue repair and exert immunomodulatory effects. Accordingly, a great deal of research has gone into optimizing MSC homing and increasing their secretion of therapeutic molecules. A variety of methods have been used to these ends, but one emerging technique gaining significant interest is the use of ultrasound. Sound waves exert mechanical pressure on cells, activating mechano-transduction pathways and altering gene expression. Ultrasound has been applied both to cultured MSCs to modulate self-renewal and differentiation, and to tissues-of-interest to make them a more attractive target for MSC homing. Here, we review the various applications of ultrasound to MSC-based therapies, including low-intensity pulsed ultrasound, pulsed focused ultrasound, and extracorporeal shockwave therapy, as well as the use of adjunctive therapies such as microbubbles. At a molecular level, it seems that ultrasound transiently generates a local gradient of cytokines, growth factors, and adhesion molecules that facilitate MSC homing. However, the molecular mechanisms underlying these methods are far from fully elucidated and may differ depending on the ultrasound parameters. We thus put forth minimal criteria for ultrasound parameter reporting, in order to ensure reproducibility of studies in the field. A deeper understanding of these mechanisms will enhance our ability to optimize this promising therapy to assist MSC-based approaches in regenerative medicine. : Abstract : Mesenchymal stromal cells (MSCs) are a promising platform for regenerative medicine, but their therapeutic efficacy still requires optimization. Ultrasound (US) can enhance MSC-based therapies through a variety of strategies. When applied to MSCs in vitro, US modulates self-renewal and differentiation. When applied to target organs in vivo, US enhances MSC homing by upregulating local cytokines and adhesion molecules.